GOVERNMENT INTERVENTION IN INDUSTRIAL R&D SOME LESSONS FROM THE INTERNATIONAL EXPERIENCE FOR INDIA - Sunil Mani (Centre for Development Studies-WP281, 1997)
There is now substantial empirical evidence, based essentially on the experience of developed countries, that there is underinvestment in industrial R&D consequent to the gradual withdrawal of the state. It is generally observed that government can solve this problem of underinvestment in two ways: by increasing the profits of innovators, or by undertaking R&D in areas where the private sector underinvests. An examination of the nature of government intervention in developed countries show that it is increasingly moving towards the latter variety. However, contrary to normal impression, the extent of government intervention in industrial R&D in India is of the former variety. The state has been using tax incentives as the major instrument for stimulating R&D by production enterprises. Direct grants, which has become the dominant instrument of intervention in the west, is considered to be better as it can be targeted towards specific projects. In fact the efficacy of tax incentives to encourage R&D requires further scrutiny. The state in India also have to intervene for making available technically trained manpower to engage in industrial R&D radically redesigning the higher education system, by improving the incentive system for those working in the R&D system etc. The paper thus underscores the fact that there is enough space for the Indian state to increase its interventionist role in industrial research contrary to the arguments for its gradual withdrawal.